An Analysis of the Role of Pragmatics in Language Learning and Teaching - Rahmawati, Rahmawati; Siregar, Elvi Fauziah; Rianto, Didik; Octaweni, Aisyah (International Journal of Educational Research Excellence, 2026)
The objective of this descriptive qualitative research is to analyze the role of pragmatics in language learning and teaching . The data of this research is the literature studies. The data sources of this research are journals, books, and articles about pragmatics. Pragmatics is a very crucial thing in language learning because it teaches learners to use language effectively in real-world contexts, going beyond grammar to convey and understand intended meanings, politeness, and cultural nuances, preventing misunderstandings and enabling successful intercultural communication. It bridges the gap between literal words and actual meaning. The role of pragmatics are to contextual understanding, avoids misunderstandings, enhances intercultural communication, develops communicative competence, and improves social confidence. Developing the pragmatics in teaching and learning process can avoid the misunderstanding in transferring ideas, thoughts, expressions, feelings, and manner. Teaching English is not just about making sentences which are correct grammatically but appropriately used in social context. In teaching pragmatics, teacher can adapt some fun activities in the classroom such as role-play, Discourse completion task, and pragmalinguistics. It can make students feel secure and have a good manner to interact with community.